1995
DOI: 10.1006/icar.1995.1120
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Pressure, Poynting-Robertson Drag, and Solar Wind Drag in the Restricted Three-Body Problem

Abstract: In this paper, we examine the effects of radiation pressure, © ,_sAcidic P_, i_. Poynting-Robertson (PR)drag

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 16 publications
4
56
0
1
Order By: Relevance
“…This feature enables using an application of adiabatic invariant theory presented in Gomes (1995) to prove that during the libration around an equilibrium point on the stable part of an equilibrium branch the libration amplitude must always increase. However, we can confirm result of Liou et al (1995) that it is impossible for a dust particle to drift toward and get trapped in the 1/1 resonance when the dust particle is approaching under the PR effect and radial stellar wind. We found that such a capture is possible after close encounter with the planet.…”
Section: Equilibrium Points With Velocity Termssupporting
confidence: 65%
See 3 more Smart Citations
“…This feature enables using an application of adiabatic invariant theory presented in Gomes (1995) to prove that during the libration around an equilibrium point on the stable part of an equilibrium branch the libration amplitude must always increase. However, we can confirm result of Liou et al (1995) that it is impossible for a dust particle to drift toward and get trapped in the 1/1 resonance when the dust particle is approaching under the PR effect and radial stellar wind. We found that such a capture is possible after close encounter with the planet.…”
Section: Equilibrium Points With Velocity Termssupporting
confidence: 65%
“…13). The dependence on the velocity of the dust particle with respect to the center of mass of the two-body system in the PR effect and the radial solar wind was also used in Liou et al (1995). They numerically obtained positions for the equilibrium points for β ∈ {0, 0.1, 0.2, ..., 0.9}.…”
Section: Equilibrium Points With Velocity Termsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ring was observed by satellites IRAS (Brownlee 1994;Dermott et al 1994) and COBE (Reach et al 1995). The orbital evolution of interplanetary dust particles near zones of mean motion resonances was investigated in many papers (Weidenschilling & Jackson 1993;Beaugé & Ferraz-Mello 1994;Šidlichovský & Nesvorný 1994;Liou et al 1995;Liou & Zook 1999;Kuchner & Holman 2003;Klačka & Pástor 2004). Liou & Zook (1997) derived the relation between the secular time derivative of eccentricity and the secular time derivative of the inclination of dust particles in mean motion resonance with a planet in a circular restricted three-body problem with the P-R effect and the radial solar wind (the authors incorrectly accounted for the radial solar wind).…”
Section: Introductionmentioning
confidence: 99%